Law Enforcement and Public Health: Partners for Community Safety and Wellbeing - Bartkowiak-Théron, Isabelle; Clover, James; Martin, Denise; Southby, Richard F.; Crofts, Nick (Springer International Publishing, 2022)
PART I - HISTORICAL AND CONCEPTUAL ISSUES -- Chapter 1. Conceptual and practice tensions in LEPH: Public health approaches to policing and Police and public health collaborations -- Chapter 2. The historical public health and social work role of the police -- Chapter 3. Defund, Dismantle or Define -- Chapter 4. Law Enforcement, Public Health, and Vulnerability -- Chapter 5. Challenges and Opportunities in Educating Law Enforcement Officers: 2020 and Beyond -- Chapter 6. Historical and Conceptual Issues: Community Voices -- PART II - LAW ENFORCEMENT AND PUBLIC HEALTH: PARTNERSHIPS AND COLLABORATIONS IN PRACTICE -- Chapter 7 - Improving Community Outcomes and Social Equity Through Leveraged Police Leadership -- Chapter 8. Law enforcement and mental health: The missing middle -- Chapter 9. The challenges of sustaining partnerships and the diversification of cultures -- Chapter 10. Using public health concepts and metrics to guide policing strategy and practice: The case for an academic center for policing and public health -- Chapter 11. Law Enforcement and Public Health Partnerships and Collaborations in Practice: Community Voices -- PART III - SPECIAL ISSUES IN LAW ENFORCEMENT AND PUBLIC HEALTH -- Chapter 12. Moving Beyond the War on Drugs? The Rhetoric and Reality of Harm Minimisation in Australia -- Chapter 13. Refugees: sitting at the nexus of law enforcement and public health. Chapter 14. First responders stress and resilience as a matter of the public health: A Scientific Approach to Police Commander's Testimonial about Police Work Challenges following Practical Implications -- Chapter 15. Law enforcement and public health: a framework for analysis of LEPH in lower- and middle-income countries (LMICs) -- Chapter 16. Policing pandemics: developing effective policing responses during health emergencies.